2019
DOI: 10.1167/19.6.18
|View full text |Cite
|
Sign up to set email alerts
|

Caricaturing can improve facial expression recognition in low-resolution images and age-related macular degeneration

Abstract: Caricaturing can improve facial expression recognition in low-resolution images and age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…The studies routinely found significant negative effects under simulation (e.g., slower speed, reduced accuracy) on the respective measured outcomes (see Table 1; Copolillo et al, 2017;Gupta et al, 2018;Lane et al, 2019). For instance, reading focused simulation studies found an expected decrease in reading performance (Wensveen et al, 1995;Gupta et al, 2018;Krishnan et al, 2019), whilst facial recognition studies showed the typical decline in face and emotional perception as simulation of AMD worsens (Irons et al, 2014;McKone et al, 2018;Lane et al, 2019;de Boer et al, 2021). These findings are not surprising as they correspond with similar research findings in AMD populations (Taylor et al, 2018b;Varadaraj et al, 2018).…”
Section: What Can We Learn From Simulations?supporting
confidence: 67%
See 3 more Smart Citations
“…The studies routinely found significant negative effects under simulation (e.g., slower speed, reduced accuracy) on the respective measured outcomes (see Table 1; Copolillo et al, 2017;Gupta et al, 2018;Lane et al, 2019). For instance, reading focused simulation studies found an expected decrease in reading performance (Wensveen et al, 1995;Gupta et al, 2018;Krishnan et al, 2019), whilst facial recognition studies showed the typical decline in face and emotional perception as simulation of AMD worsens (Irons et al, 2014;McKone et al, 2018;Lane et al, 2019;de Boer et al, 2021). These findings are not surprising as they correspond with similar research findings in AMD populations (Taylor et al, 2018b;Varadaraj et al, 2018).…”
Section: What Can We Learn From Simulations?supporting
confidence: 67%
“…Yet, the recruitment of younger participants is not unusual for all types of simulation studies (Wood et al, 2012;Hwang et al, 2018). In this review, four studies compared younger and older normally sighted adults under simulation (Wensveen et al, 1995;Kwon et al, 2012;Krishnan et al, 2019;Lane et al, 2019). They found significantly decreased performance for both age groups under simulation, but comparatively worse performance for the older adults.…”
Section: Comparison Of Simulation Methods Validation and Adaptation Proceduresmentioning
confidence: 95%
See 2 more Smart Citations
“…Age-related macular degeneration (AMD) is the leading cause of vision loss in the Western world, 1 leading to poor quality of life outcomes especially for reading, driving, and looking after oneself. 2 4 Recent advances in managing early stages of AMD 5 and treatments for end stage geographic atrophy are currently being explored (ARVO abstract: 2019, 4983). Previous studies have investigated impaired visual acuity (VA), 6 dark adaptation, 7 flicker thresholds, 8 photostress recovery time, 9 and microperimetry in AMD.…”
Section: Introductionmentioning
confidence: 99%